A tese como obra de arte na era de sua reprodutibilidade tecnica - Guimarães, Nathalia Muylaert Locks [UNESP] (2016)
The objective of this thesis was to create a virtual prototype thesis, which is in accordance with the new forms of content production. The creation of this prototype, which is nothing more than the implementation of a written thesis in the form of blog, allows the University to appropriate web space, since the University has lost its role as a training institution. In an age of information overload, where ordinary users appropriated the freedom to create content filter through necessary information becomes a problem. Umberto Eco, in a text on the role of universities, compared to the mass media phenomenon, says it is "necessary to invent, and impart a new art clearance", which this prototype is to be objective. That's why we call the thesis as a work of art, for the paper, the text, the standard needed to be reinvented for possible ownership of the world wide web space. Then reinforcing the technical reproducibility of the argument, urging the reader to lead to carry out its own mediation immanent way. Thus, the parody of text Walter Benjamin The Work of Art in the Age of Mechanical Reproduction (1936), parodied as The thesis as a work of art in the age of technical reproducibility; critical, not discursive form, the norms of abnt, combining the problem of quantity instead of quality to their way of exposure and data compilation. In this sense, the footnote, citation, among other standards abnt are thought in a virtual dimension. Number of pages become unnecessary when you can install a tool search. Thus, this study presents the following manner: 1) Thesis Virtual and Critique of abnt: Where has the methodology that was presented by version 1.02 (printed version, and transmedia, moving between the role of information and virtual content via QR-codes). Followed, the presentation of the virtual prototype (version 2.0) finalized on defense on June 9, 2016. And the preparation of the thesis manual work written accordly the rules of ABNT (version 2.1) to deposit in the library of the University. 2) Own content production: Where to apply the methodology of the thesis as work in the production of innovative content developed here as Critical Theory of Racket considering as the basis of development, the Free Software ideological conception (creative commons and copyleft) and Critical to the Critical Theory and the Traditional Theory by Frankfurt School.